การศึกษาปรากฏการณ์ทัศนศาสตร์แม่เหล็กของเคอร์แบบตามขวางในแม่เหล็กเฟอร์โร - พงษ์หิรัญ ทรงศักดิ์ (Science Essence Journal, 2011)
อันตรกริยาของแสงโพลาไรซ์กับตัวกลางที่มีสภาพความเป็นแม่เหล็กสามารถทำให้เกิดการเปลี่ยนแปลงสมบัติทางแสงและทางแม่เหล็กของตัวกลางนั้นได้ การเปลี่ยนแปลงสมบัติเหล่านี้ขึ้นอยู่กับสถานะทางแม่เหล็กของวัสดุและสามารถแสดงออกมาในรูปของปรากฏการณ์ทัศนศาสตร์แม่เหล็ก ซึ่งจะนำไปสู่การศึกษาสมบัติทางแม่เหล็กของวัสดุได้ สารแม่เหล็กประเภทเหล็กและนิเกิลถูกใช้เป็นสารตัวอย่างฟิล์มบางในการทดลอง และสามารถแสดงถึงคุณลักษณะที่แตกต่างกันของปรากฏการณ์ทัศนศาสตร์แม่เหล็กที่เกิดขึ้น การศึกษาสมบัติทางแม่เหล็กและทางจุลภาคโดยใช้กล้องจุลทรรศน์แรงอะตอม สามารถพบการเกิดแมกเนไทเซชั่นอิ่มตัวของวัสดุทั้งสองในสนามแม่เหล็กที่ต่ำ The interaction of polarized light with magnetized media may change the optical and magnetic properties of the media. The change of those properties depends on their magnetic state and manifests in the form of a magneto-optical effect, which can be used to study the magnetic properties of materials. Magnetic materials such as Fe and Ni were used as thin film samples in this experiment. The results demonstrate the different characteristics of magneto-optical effects in different materials. Studies of the magnetic properties and micro-structures by atomic force microscopy (AFM) show and confirm that the magnetization saturation of these samples can be observed in low magnetic fields.